Carbon, Nitrogen and Hydrogen in Iron-Based Solid Solutions: Similarities and Differences in their Effect on Structure and Properties - Gavriljuk, V.G. (Металлофизика и новейшие технологии, 2016)
Interstitial N, C and H atoms in iron-based solid solutions are compared in terms of their effect on the structure and properties. Electronic structure and stacking fault energy, atomic distribution, interaction of interstitial atoms with dislocations and vacancies, mobility of dislocations, mechanisms of deformation and fracture are compared based on theoretical calculations and experimental observations. As shown, nitrogen and hydrogen increase the electron density of states at the Fermi level of f.c.c. iron, whereas carbon decreases it. Correspondingly, the concentration of free electrons increases within the nitrogen and hydrogen iron-based solid solutions and decreases in the carbon ones. A correlation is revealed between the character of interatomic bonds and the short-range atomic order in the studied solid solutions: nitrogen assists short-range atomic ordering in the spatial distribution of alloying elements, whereas carbon promotes their clustering. As consequence, nitrogen increases thermodynamical stability of austenitic steels, whereas carbon makes steel sensitive to precipitation of carbides from the solid solution that deteriorates corrosive characteristics. The most impressive is a correlation between the change in the electronic structure and properties of dislocations. In contrast to prevailing covalent bonds in carbon steels, the enhanced metallic character of interatomic bonds, as caused by nitrogen, increases mobility of dislocations that results in excellent plasticity and fracture toughness. However, the same effect caused by hydrogen is a cause of the hydrogen embrittlement through the hydrogen-enhanced localized plasticity. A unique similarity with hydrogen embrittlement becomes apparent in the course of impact loading of austenitic nitrogen steels, where, due to the absence of sufficient time for relaxation of stresses, the nitrogen-enhanced localized plasticity occurs resulting in a pseudo-brittle fracture. The different is only the mechanism for localization of plastic deformation: the shortrange atomic ordering caused by nitrogen and the increased concentration of superabundant vacancies due to hydrogen dissolution.